The Role of Supervision: Is it Still Optimal in the Assistant Lecturer Corps? - Yokhebed Widhianingtyas; Christian Alessandro Noreen; Aprina Nugrahesthy Sulistya Hapsari (Asia Pacific Fraud Journal, 2022)
This research aims to describe the monitoring function of operational activity in the Assistant Lecturer Corps of the Faculty of Economic and Business (FEB), Satya Wacana Christian University (UKSW). The operational activity of the Assistant Lecturer Corps of the Faculty of Economic and Business is divided into two general activities: plotting activity and financial activity. This research uses interviews with Assistant Coordinator, ex Assistant Coordinator, student, and Deputy Dean as interviewees. Furthermore, this research uses Assistant Coordinator Report and Standard Operational Procedure (SOP) as literature review. The result of this paper shows that supervision has already done in plotting and financial activities. Nevertheless, the implementation of supervision as an internal control is not optimum due to the availability of harmful fraud risk. The Assistant Lecturer Corps’ SOP policy is irrelevant and not implemented properly. Furthermore, there is no integrated information system for monitoring the activity.